POLA KONSUMSI PROTEIN DAN KADAR ASAM URAT PADA PENARI KECAK SAHADEWA BARONG DAN KERIS DANCE - Anak_Agung Made Kartika_Dewi; Gusti_Ayu Dewi Kusumayanti; Pande_Putu Sri Sugiani (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
National prevalence for joint disease is 30.3% (based on diagnosis by health professionals and symptoms). The purpose of this study was to determine the pattern of protein consumption and uric acid levels in kecak dancers in Sahadewa Barong and Kris Dance. This type of research is observational research with cross sectional approach. Data on protein consumption was collected by the SQ-FFQ method, while the measurement of uric acid levels was carried out using a multi-parameter check tool. The data that has been collected is then made into a cross table.The results of data from 47 samples seen from the pattern of protein consumption most of the samples had consumed 2 types of protein (95.74%), in terms of the amount of protein consumed, most of the samples still consumed less protein than needed (82.98%) and in terms of the frequency of most samples often consuming protein (59.57%). The results of the cross tabulation analysis found that most of the samples had normal uric acid levels (80.85%). Most of the samples that consumed more protein than needed had high uric acid levels (55.56%). It is expected that kecad sahadewa barong dancers and kris dances pay more attention to the amount, type and frequency of protein intake. Keywords: protein consumption, uric acid levels